The Paradox of ApoA5 Modulation of Triglycerides: Evidences from Clinical and Basic Research - Garelnabi, Mahdi (2012)
Apolipoprotein A5 (ApoA5) is a key regulator of plasma triglycerides (TG), although its plasma concentration is very low compared to other known apoproteins. Over the years, researchers have attempted to elucidate the molecular mechanisms by which ApoA5 regulates plasma TG in vivo. Though still under debate, two theories broadly describe how ApoA5 modulates TG levels: (i) ApoA5 enhances the catabolism of TG-rich lipoproteins and (ii) it inhibits the rate of production of very low-density lipoprotein (VLDL), the major carrier of TGs. This review will summarize the basic and clinical studies that have attempted to describe the importance of ApoA5 in TG metabolism. Population studies conducted in various countries have demonstrated an association between single nucleotide polymorphisms (SNPs) in ApoA5 and the increased risk to cardiovascular disease and metabolic syndrome (including diabetes and obesity). ApoA5 is also highly expressed during liver regeneration and is an acute phase protein associated with HDL which was independent of its effects on TG metabolism. CONCLUSION: Despite considerable evidences available from clinical and basic research studies, on the role of ApoA5 in TG metabolism and its indirect link to metabolic diseases, additional investigations are needed to understand the paradoxical role of this important apoprotein shown modulated by diet and from it polymorphism variants.